National Participatory Project and its Influence on National Development and Defense - Palomino Duarte, Julio Edilberto (2019)
Peru is currently discussing the definition of socio-economic development and its inherent elements. In that order, citizen participation constitutes a fundamental component in the construction of integral development strategies and national security and defense, based on the knowledge of the processes of analysis of national problems and the definition of transformation requirements, mediated by the strengthening of the organizational capacities of the agents of the process. The main objective of this research is to determine the extent to which a National Participatory Project influences National Defense and Development. The research methodology was of a non-experimental, quantitative, descriptive and applicative design, with a sample of 116 officials from the Presidency of the Council of Ministers and the Ministry of Defense, responsible for the management of strategic projects in the country. The data collection technique applied corresponds to the survey and observation. The study concluded that the level of a National Participatory Project influences national development and defense, the country’s economy, social development and the country’s governance process. As a corollary, a proposal for a National Participatory Project (PNP) is presented, structured on the basis of two objectives: 1. Optimize negotiations in the management of projects with agents subject to participation, 2. Optimize project management.